Enclaves van leed en werkelijkheid; wiens trauma is 'Srebrenica' eigenlijk? - B.G.J. de Graaff (BMGN: Low Countries Historical Review, 2006)
R. van den Boogaard, Zilverstad. De Haagse verduistering van het drama-Srebrenica C. Banning, P. de Koning, Balkan aan de Noordzee. Over het Joegoslavië-tribunaal, over recht en onrecht H. Praamsma, J. Peekel, T. Boumans, Herinneringen aan Srebrenica. 171 Soldatengesprekken E. Suljagic, E. Vulliamy, L. Haveric, Postcards from the grave, afterword by Vulliamy, E., translated by L. Haveric L.P.C. Ruigrok, Journalism of attachment. Dutch newspapers during the Bosnian war A. van Loon, Vrouwen van Srebrenica J. VanIerberghe, Kroniek van onmacht. Sarajevo, Srebrenica... tien jaar later   Bob de Graaff, Enclaves of truth and anguish; whose trauma is ‘Srebrenica’ anyway? In 2005,ten years after the fall of the so-called ‘safearea’ of Srebrenica where a Dutch UN-battalion had been deployed to deter a Serb attack on the Bosnian Muslim enclave, several books were published on the war in Bosnia-Herzogovina (1992-1995). These publications examined the war’s aftermath and the way in which people came to terms with it. The author shows how the different groups involved in the tragedy at the time  Bosnian Muslims and Dutch politicians, journalists and soldiers  – all had their own separate ways of committing their pain to memory, there by giving the impression that each one of them had a monopoly on the truth and that their traumatic experience was unique.